PERANAN ARTHROPODAA DI EKOSISTEM EKOTON DAN KELAPA SAWIT The Role of Arthropodas in Ecotone and Oil Palm Ecosystems - Noor Farikhah Haneda; Cahyo Wibowo; Muhammad Hasbi (Jurnal Silvikultur Tropika, 2017)
Forest land conversion into oil palm plantation causes drastic ecological changes which influence various species in the ecosystem. Arthropoda, as one of the components of biodiversity, has important roles as herbivore, predator and parasitoid, and detritivore. This research was conducted in village of Runtu, Subdistrict of Arut Selatan, District of Kotawaringin Barat, the province of Central Kalimantan. Techniques of Arthropoda sample collection were pitfall trap, malaise trap, and sweep net conducted in two ecosystems. The two ecosystems were ecotone (transition between forest and oil palm plantation) and oil palm plantation. Research results showed that forest existence could increase the abundance of arthropoda. Abundance of Arthropoda in ecotone ecosystem was higher as compared to that in oil palm plantation. Populations of predator and parasitoid Arthropoda were higher in ecotone ecosystem.Key words: Arthropoda, detritivore, herbivore, oil palm plantation, predator, parasitoid